Future of ERP systems - Bagó, Péter; Horváth, G. (Acta Agraria Kaposváriensis, 2010)
There are some new reflections about enterprise resource systems, like e-commerce, mcommerce and c-commerce. All of these processes, a direct consequence of the developing world, the globalization of businesses, attract them to the improvements and the related technology. However, the leading ERP systems, little is said about the environmental processes and solutions. Permeates the lives of today's environment, environmental behavior, which is increasingly required by law, it is important that the use of their ERP systems, they can be incorporated into the process with these guidelines. Several solutions were the environmental behavior of companies to manage, such as EMS (environmental management system), which is standard and basic organizational tool, which established the basis of EMAS or 14 001 ISO standards. Few systems on the market, which is a comprehensive solution for eco-action in order to ERP II has such a direction to go in the future, studies will be the presentation of options, creating a theoretical model that e-awareness of ERP as I would like to put in place.
Keywords: ERP; e-commerce; m-commerce; c-commerce; ERPII